FORTIFIKASI I ODIUM DALAM GULA KELAPA DAN KESTABILAN'NYA DALAM PROD UK PANGAN - Rumpoko Wicaksono; Rifda Naufalin; Hidayah Dwiyanti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
Iodine fortification of brown sugar is an effort to improve variation ofiodized foods in preventing iodine deficiency disorders in Indonesia. This research aimed to: a) study the effect of fortification time(iodine addition) in iodized brown sugar processing on iodine retention in product; b) deter• mine the source ofiodine that suitable for iodine fortification ofbrown sugar; c) study the packaging type that can retain iodine stability of iodized brown sugar during storage; d) study the effect of iodized brown sugar usage in making of